Reconstruction with β-tricalcium phosphate for giant cell tumor of the talus. (March 2020) - Sakamoto, Akio; Okamoto, Takeshi; Matsuda, Shuichi
Highlights: Giant cell tumor of bone (GCTB) is a locally aggressive tumor, extending from the metaphysis to the subchondral bone. GCTB is uncommon in the small bones of the foot, including the talus. Low porosity β-tricalcium phosphate (TCP) (hard-type β-TCP) has strong compressive resistance. A reconstruction with hard-type β-TCP is used in the talus after curettage of GCTB. Abstract: Giant cell tumor of bone (GCTB) is a locally aggressive tumor, commonly occurs in the long bones, and is rare in the talus and the foot. The talus is a weight-bearing bone and strut reconstruction is preferred. Reconstruction with low porosity β-tricalcium phosphate (β-TCP) blocks is reported for GCTB in the knee. In the current report, a 25-year-old female suffered from GCTB in the talus extending to the subchondral bone. The tumor was treated by curettage and the bone was reconstructed with low porosity β-TCP blocks, which have strong compressive strength. The implanted β-TCP blocks were incorporated successfully. The current reconstruction method can be applied for GCTB in the talus.